The Third Mission of Universities on the African Continent: Conceptualisation and Operationalisation - Nabaho, Lazarus; Turyasingura, Wilberforce; Twinomuhwezi, Ivan; Nabukenya, Margaret (Higher Learning Research Communications, 2022)
The purpose of the study was to explore the conceptualization of the third mission in African higher education and the activities that universities are required to engage in and/or are engaging in to fulfil the third role. Method: The interpretive lens underpinned the study. Data were collected from the documents of the African Union Commission (AUC), in which the third mission is both implicit and explicit. We used content analysis as a data analysis technique. Results: The AUC conceptualizes the third mission as a role of universities, as a social role, as forging partnerships, and as being mutually beneficial to society and the university. Universities in Africa are implementing and/or required to implement 11 third mission activities aimed at bridging the gap between them and society. Almost all third mission activities are anchored to the classical missions of teaching and research associated with higher education institutions. Conclusions: We concluded that: (a) the third mission is built on the classical missions of universities; (b) the distinction between the classical missions and the third mission is that the first mission (teaching) involves the dissemination of knowledge through academic education while the second mission (research) hinges on the generation of academic knowledge, but the third mission involves both in a non-academic context; and (c) the third mission is a multidimensional concept. Implication for Theory and Practice: The study adds to the limited literature on the third mission of universities from a supranational perspective. Second, it extends the conceptual framework of Molas-Gallart
Keywords: universities; third mission; conceptualization; contestations